THE EFFECT OF EXPERIENTAL MARKETING, SERVICE QUALITY AND PROMOTION ON CUSTOMER LOYALTY AT ROLAND BAKERY AND CAFE JEMBER - Bella Aurellia Natalie; J. E. Sutanto; Moses Soediro; Adrie Oktavio (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Research entitled